Animals in Tradition and Culture: An Ethnozoological Study of the Indigenous People of Seram Island - Marthina Tjoa; Rony Marsyal Kunda; Henderina Lelloltery; Maya MS Puttileihalat (Postgraduate, University of Mataram, 2025)
This study aims to examine the relationship between the indigenous people of Seram Island and several species of animals that are utilized for socio-cultural purposes and how the practice of ethnozoology can contribute to sustainable conservation efforts. The research was conducted using an ethnographic approach through in-depth interviews with purposively selected respondents. Qualitative descriptive analysis was conducted systematically based on themes that bind the types of animals studied. The results showed that the practice of ethnozoology includes utilization for ritual purposes related to local community belief values. Some animal species that are utilized for special purposes include Cuscuses (Phalanger spp.) and wild boar (Sus scrofa) which are useful for traditional ceremonies. The animals are killed and the meat is divided to be eaten during the ceremony. Gosong Bird (Eulipoa wallacei) as a Season Marker helps the community in managing agricultural land, marked by the presence or absence of these animals at certain locations. Deer (Rusa timorensis) as a Source of Food and Social Status by utilizing its meat. Cassowary (Casuarius spp.) as a symbol of strength. Hornbill (Rhyticeros plicatus) as a symbol of longevity. These animals are utilized by indigenous people not only for traditional rituals but also for animal protein needs such as cuscuses, Wild Boar and Deer. The needs of the indigenous community for the aforementioned animals have encouraged the community to maintain and preserve them based on their local wisdom such as the application of Sasi.